UPAYA PENINGKATAN SATUAN SAMAPTA MELALUl PATROLl RODA EMPAT GUNA MENCEGAH TlNDAK PlDANA PENCURlAN Dl WlLAYAH HUKUM POLRES BOYOLALl - ANNISA ANNISA (Police Studies Review, 2022)
ABSTRACT SATUAN SAMAPTA'S EFFORTS THROUGH FOUR-WHEELED PATROLS TO PREVENT THEFT IN THE JURISDICTION OF BOYOLALI POLICE Annisa, 18,229. annisaku73@gmail.com This final task is motivated by the increase in ordinary theft crimes in Boyolali Regency from year to year. Therefore, this study agreed to describe the extent of patrols at Boyolali Police Station in preventing ordinary theft and knowing what efforts have been made by patrol units. The theories and concepts used by the author in answering these problems are POAC management theory and its management elements (man, money, method, materials). Then for the concept used is the concept of theft, the concept of technical functions samapta and the concept of patrol. Furthermore, this research is carried out with a qualitative approach and uses the type of field research (field research). The findings of this study are in the implementation of patrols and efforts to prevent theft are usually carried out with the analysis of Perkabaharkam No. 1 of 2017 on patrols and Perpol No. 2 of 2021 concerning SOTK Polres and Polsek. The result of the research conducted by the author is that the completeness of administration before the implementation of patrols is still not good such as warrants issued after the implementation of patrols, lack of personnel from the Personnel Array List (DSP), while for budgets and infrastructure have been met but need maximum use. As well as the need to conduct specialization development education and training for patrol members. For the conclusion that can be taken that the implementation of patrols has not been carried out optimally in preventing ordinary theft, there are still some inhibitory factors that become obstacles in the implementation of patrols. Therefore, the author suggests that personnel proposals be carried out according to the Personnel Composition List (DSP) and maximize the use of existing facilities and infrastructure and maximize personnel performance to participate in specialization development education (dibangspes) and training. In addition, it increases cooperation between personnel and the community. Community peran is also no less important in the prevention of ordinary theft crimes. Keywords : effort, patrol satsamapta, usual theft prevention, Polres Boyolali